Trabectedin in advanced desmoplastic round cell tumors: a retrospective single-center series. Issue 1 (January 2017) - Verret, Benjamin; Honore, Charles; Dumont, Sarah; Terrier, Philippe; Adam, Julien; Cavalcanti, Andrea; Sourrouille, Isabelle; Klausner, Guillaume; Ahlenc-Gelas, Marion; Kiavue, Nicolas; Domitrescu, Gabriella; El Amarti, Lamiae; et al.
Abstract : Desmoplastic small round cell tumor (DSRCT) is a rare and aggressive malignancy that occurs with unpredictable chemosensitivity and limited treatment options in the advanced setting. Prognosis is poor, and exploring new treatment options for such diseases is difficult because of its rarity. Clinical activity of trabectedin for advanced DSRCT was scarcely reported in the literature. Here, we report a series of six patients treated with trabectedin for an unresectable DSRCT. After receiving trabectedin, two patients had stable disease with a time to progression of 3 and 3.5 months; four patients experienced disease progression after one cycle, two of them could receive one and two patients another line regiment. Four patients experienced grade 3–4 adverse events, two grade 3 thrombocytopenia, and one neutropenic fever. Prognosis was poor with a median overall survival of 4 (range: 2–14) months. In our experience, trabectedin had limited activity in advanced DSRCT. Further studies are warranted to find effective treatments.